KAJIAN KETELITIAN PLANIMETRIK BANGUNAN RUMAH MENGGUNAKAN CITRA IKONOS TIPE GEOMONO - Martono, Dwi Nowo (Institut Teknologi Sepuluh Nopember, 2007)
Very high spatial resolution of remote sensing data have been used in many planning and evalution at detail settlement area. Therefore geometric accuracy of formal and informal housing at Sub-Province of Bekasi. Procedure research cosist of digital image processing, visual interpretation and delineation of formal and informal housing, while accuracy analysis which it's comparison by field survey. Result interpretation and delineation of building housing area have achieve acuracy 88%. This is indicating that very high spatial resolution remote sensing data have useful and suitable for application are related of detail aspect.